A Cloud-Scale View of the Molecular Gas Disk in the Whirlpool Galaxy and Beyond - Schinnerer Eva; Pety Jérôme; Bešlić Ivana; Eibensteiner Cosima; Stuber Sophia; Leroy Adam; Hughes Annie; Usero Antonio; Bigiel Frank (EPJ Web of Conferences, 2022)
The nearby galaxy M51 (also known as the Whirlpool galaxy) hosts an iconic grand-design spiral pattern and both IRAM facilities conducted the first cloud-scale (∼50 pc resolution) survey of the molecular gas reservoir across a the disk of a massive star-forming galaxy (PAWS, PdBI+30m Arcsecond Whirlpool galaxy Survey) using the CO(1-0) line emission. PAWS showed that the various properties of the giant molecular cloud (GMC) population vary with galactic environment (center/bar, spiral arms, inter-arm). Recent observations of a ∼1000 pointing mosaic of the nearby late-type spiral galaxy IC342 using NOEMA resolved its GMC population at ∼70 pc resolution and find consistent trends. Investigation of the dense molecular gas phase at cloud-scales using tracers such as HCN(1-0) confirms the trends seen in kpc-scale surveys, namely that the dense gas star formation efficiency inn general apparently anticorrelates with the inferred dense gas fraction. Multi-line studies of the molecular gas in the galactic disks of nearby galaxies such as the ongoing large NOEMA+30m program to map the dense molecular gas phase in GMCs in the central part of M51 will allow for gaining new insights of the properties of this important molecular gas phase.